(untitled) (Global Journal of Human-Social Science, 2011)
Inclusion at school can be seen constituting of small but significant issues such as the participation in the learning community the experiences of success and studying and playing together with classmates An instruction strategy which takes into consideration pupils different learning phases and aims to their participation was constructed in this research As a theoretical framework the Universal Design for Instruction UDI and Vygotsky s zone of proximal development was applied The study method was collaborative action research The teacher-researcher collected the data during mathematics and mother tongue lessons in an inclusive elementary class and the study was a part of a large empiric development project that aimed at combining the knowledge and know-how from the fields of special education and general education into participatory basic education Co-operative teaching was a crucial underlying support for the strategy and the whole inclusive approach The findings were explicated and drafted through examples of teaching and learning situations carried out during the research In this study a three-level framework for inclusive pedagogies was constructed